(untitled) (Zamonaviy ilmiy-texnik tadqiqotlar, 2026)
The article describes the features and practical aspects of the processes of social adaptation of children with disabilities. The necessary and scientific advice was given to social workers and sociologists on how to communicate with children with disabilities and create opportunities for them to become full members of society. This article outlines key decisions to improve the lives of children with disabilities, which are now relevant in public life. The article notes that there are ways to return children with disabilities to a healthy life and social work. In particular, recommendations are given on protecting the rights of these children during treatment.